Research on the Radial Accuracy of Ultrasonic Vibration-Assisted Single Point Incremental Forming Parts - Yang Mingshun; Bai Lang; Lin Yunbo; Li Yan; Yuan Qilong; Zhao Renfeng (International Journal of Aerospace Engineering)
With the more and more complexity demands of the market, the geometric accuracy of the part has become the main factor restricting the development of single point incremental forming technology (SPIF). For this reason, with the truncated cone as the target part, the radial accuracy error generation mechanism was analyzed from the aspects of sheet springback and residual stress distribution. Four factors and three levels of surface response experiments were designed using the Box-Behnken Design (BBD) for tool head diameter, layer spacing, sheet thickness, and wall angle. The single and interactive influence law of the process parameters on the radial accuracy was obtained. In response to the above research results, the ultrasonic vibration was introduced into the process of SPIF to reduce springback by reducing residual stress. The influence of vibration parameters on the accuracy was obtained through experiments. The results showed that ultrasonic vibration could effectively improve and control the accuracy of the part.